2009
DOI: 10.1177/0363546508328112
|View full text |Cite
|
Sign up to set email alerts
|

Wrist Injuries in Nonprofessional Tennis Players: Relationships with Different Grips

Abstract: In nonprofessional tennis players with wrist injuries, different grips of the racket are related to the anatomical site of the lesion: Eastern grip with radial-side injuries and Western or semi-Western with ulnar-side injuries. Knowledge of this relationship may influence training, prevention, diagnosis, and therapy of wrist problems in nonprofessional tennis players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 19 publications
0
44
0
Order By: Relevance
“…It is also known as "hammer grip" because it is naturally obtained when holding the racquet as if it were a hammer. The base knuckle of the index finger is placed on bevel number 2 of the tennis racquet grip, and the heel pad of the hand is placed between bevels number 1 and 2 (e.g., Tagliafico, Ameri, Michaud, Derchi, Sormani, & Martinoli, 2009). Participants were also asked to stand behind the middle of their baseline, with the racquet in their dominant hand and the ball in the other hand.…”
Section: Methodsmentioning
confidence: 99%
“…It is also known as "hammer grip" because it is naturally obtained when holding the racquet as if it were a hammer. The base knuckle of the index finger is placed on bevel number 2 of the tennis racquet grip, and the heel pad of the hand is placed between bevels number 1 and 2 (e.g., Tagliafico, Ameri, Michaud, Derchi, Sormani, & Martinoli, 2009). Participants were also asked to stand behind the middle of their baseline, with the racquet in their dominant hand and the ball in the other hand.…”
Section: Methodsmentioning
confidence: 99%
“…The continental grip places the second knuckle on level 1 of the grip while a full western grip has the second knuckle placed at the bottom face of the grip (figure 1A,B). 85 To investigate the effect of grip type on injury to the wrist, Tagliafico et al studied 370 non-professional tennis players 86. They found that ulnar-sided injuries (extensor carpi ulnaris tendonitis and triangular fibrocartilage complex pathology) were significantly associated with western or semiwestern grips while radial-sided injuries (flexor carpi radialis tendonitis, DeQuervian's tendinopathy and intersection syndrome) were more common in players with the eastern grip 86…”
Section: Player-specific Risk Factorsmentioning
confidence: 99%
“…Differences in skill level, court surface type, player age, and physical conditioning can further influence or complicate injury manifestation. 9,10,15,27,30 The literature on tennis injury epidemiology, though substantial in volume, is limited in scope.…”
Section: Introductionmentioning
confidence: 99%
“…15 Correlations between type of racket grip and type of wrist injury have also been described in the literature. 27 Players therefore may be able to reduce the likelihood of wrist and other types of injuries through proper training and refinement of technique. Furthermore, negative adaptations, such as reduced flexibility and asymmetric hypertrophy, can occur after repeated tennis play, increasing the risk of injury.…”
mentioning
confidence: 99%